Desenvolvimento e construção de um sistema de controle de uma fechadura elétrica para residências comandado por um celular - Silva, Julia Paschoal (Universidade Federal de São Carlos, 2021)
The present work consists in the development and construction of a prototype of an electric lock for homes, remotely controlled by cell phone using the ESP8266 NodeMcu module, a card with a Wi-Fi connection. One of the requirements is that the electric lock to be installed inside the main door of the residence, so that it is not possible to view it externally. The system contains a relay to activate the electric lock and an Android cell phone application with buttons for command to open/close the lock. The ESP8266 NodeMcu module connects via Wi-Fi to the cellphone and activates the relay through a port. Finally, sensors were installed to check whether the lock is open or closed to notify the user.
Development and construction of a control system of an electric lockfor for homes remotely controlled by cell phone
Keywords: Fechadura elétrica via Wi-Fi; Acionamento via celular; ESP8266; NodeMcu; Automação residencial; Aplicativo Android para controle residencial; Electric lock using Wi-Fi; Cellular Activation; Wi-Fi; Home Automation; Android Application; ENGENHARIAS::ENGENHARIA ELETRICA::CIRCUITOS ELETRICOS, MAGNETICOS E ELETRONICOS